Effect of Freezing-Thawing Cycle on the Mechanical Properties and Micromechanism of Red Mud-Calcium-Based Composite Cemented Soil - Hao Wen; Chongxian Suo; Yafen Hao; Peige Fan; Xiaoqiang Dong (Advances in Civil Engineering, 2020)
The environmental issues caused by solid waste have become increasingly serious. Adding additive is considered as an effective measure to improve the performance of the cemented soil. Therefore, the feasibility study of solid waste such as red mud and desulfurization gypsum used in composite cemented soil is in urgent demand. In this study, the mechanical properties and durability to freezing-thawing cycle of red mud-calcium-based composite cemented soil (RMCC) were analyzed through compressive strength test, resistivity test, and freezing-thawing cycle test. The action mechanism of RMCC was revealed through a series of X-ray diffraction (XRD) and scanning electron microscope (SEM) with energy dispersive spectrometer (EDS) test. The results show that the optimal red mud content in RMCC is 12%. As the freezing-thawing cycle progresses, the difference in resistivity and pressure sensitivity of RMCC gradually weakens. When the freezing-thawing cycle reaches 7, the pressure sensitivity characteristic of RMCC is lost. The change in resistivity and pressure sensitivity can be used to characterize the damage caused by the freezing-thawing cycle. Combined with XRD and SEM analysis, the presence of minerals such as K2Ca5(SO4)6·H2O and (Ca, Na)2(Si, Al)5O10·3H2O play a key role in fixation of alkali metal elements, and the coordination of CSH gel cementation effect and AFt filling effect has a significant impact on mechanical properties. The study provides an effective way to the utilization of red mud and desulfurization gypsum in subgrade strengthening.